An uncommon passage : traveling through history on the Great Allegheny Passage Trail - Muller, Edward K. (University of Pittsburgh Press, 2009)
The Great Allegheny Passage Trail forms a hiking and biking route stretching approximately 150 miles from Pittsburgh, Pennsylvania, to Cumberland, Maryland, where it connects with the C & O Canal Towpath to reach Washington, DC. The trail is the culmination of many years of work by the Allegheny Trail Alliance, which joined seven separate trail organizations from Pennsylvania and Maryland to acquire and develop the land. Formerly an Indian path, trade route, military road, railway link, and part of the original National Road-the trail is truly a path to American history. An Uncommon Passage guide.